2002
DOI: 10.1073/pnas.212381799
|View full text |Cite
|
Sign up to set email alerts
|

Impaired recycling of synaptic vesicles after acute perturbation of the presynaptic actin cytoskeleton

Abstract: Actin is an abundant component of nerve terminals that has been implicated at multiple steps of the synaptic vesicle cycle, including reversible anchoring, exocytosis, and recycling of synaptic vesicles. In the present study we used the lamprey reticulospinal synapse to examine the role of actin at the site of synaptic vesicle recycling, the endocytic zone. Compounds interfering with actin function, including phalloidin, the catalytic subunit of Clostridium botulinum C2 toxin, and N-ethylmaleimide-treated myos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
238
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(267 citation statements)
references
References 36 publications
28
238
1
Order By: Relevance
“…Endosomes or endocytic transport vesicles likely use cytoskeletal elements for motility (Durrbach et al, 1996;Nakagawa and Miyamoto, 1998;Durrbach et al, 2000;Neuhaus and Soldati, 2000;Lanzetti et al, 2001;Lapierre et al, 2001;Zaslaver et al, 2001;Shupliakov et al, 2002;Engqvist-Goldstein and Drubin, 2003). Actinin-4 is predicted to have an actin-binding domain, and we have observed that it binds actin (our unpublished data).…”
Section: Actinin-4 Depletion Affects Tf Traffickingsupporting
confidence: 53%
“…Endosomes or endocytic transport vesicles likely use cytoskeletal elements for motility (Durrbach et al, 1996;Nakagawa and Miyamoto, 1998;Durrbach et al, 2000;Neuhaus and Soldati, 2000;Lanzetti et al, 2001;Lapierre et al, 2001;Zaslaver et al, 2001;Shupliakov et al, 2002;Engqvist-Goldstein and Drubin, 2003). Actinin-4 is predicted to have an actin-binding domain, and we have observed that it binds actin (our unpublished data).…”
Section: Actinin-4 Depletion Affects Tf Traffickingsupporting
confidence: 53%
“…ponents of endocytosis are regulated by actin (Taylor et al, 2012), which motivated us to test for involvement of MII.…”
Section: Resultsmentioning
confidence: 99%
“…This possibility is supported by recent work showing that trafficking is MII dependent (Peng et al, 2012). While there are no data to support a role for MII in transition of vesicles between the resting pool and recently recycled pool, it is interesting to note that the key component controlling this transition, CDK5, is known to phosphorylate multiple presynaptic proteins including both dynamin-1 and the MIIB heavy chain (Tan et al, 2003;Jämsä et al, 2009). Defects in retrieval of docked vesicles that release neurotransmitter via a kiss-and-run mechanism may also prevent replenishment of neurotransmitter-loaded fusion-competent vesicles in the RRP if full collapse of vesicles does not occur.…”
Section: Synaptic Vesicle Retrieval and Its Relationship To The Rrp Sizementioning
confidence: 99%
See 1 more Smart Citation
“…However, this observation needs to be independently confirmed. Actin is known to be crucial for synaptic-vesicle recycling 104 , and synaptic-vesicle movement at presynaptic terminals that are devoid of microtubules is dependent on myosin Va 105 . Myosin Va on synaptic vesicles directly interacts, in a Ca 2+ -dependent manner, with plasma membrane syntaxin-1a through its neck domain, and is thereby proposed to regulate stimulated exocytosis through the supply of readily releasable vesicles 106 .…”
Section: Outbound Trafficmentioning
confidence: 99%